ORGANIZATION CITIZENSHIP BEHAVIOR GURU DAPAT DITINGKATKAN DENGAN KOMITMEN ORGANISASI DAN KECERDASAN SPIRITUAL - Andri Kusmayadi; Sumardi ,; Rais Hidayat; Farida Wulandari (Universitas Pakuan, 2020)
ORGANIZATION CITIZENSHIP BEHAVIOR TEACHERS CAN BE ENHANCED WITH SPIRITUAL ORGANIZATION AND INTELLIGENCE COMMITMENTSThe research aimed to find the relationship between organizational commitment and spiritual intelligence with Organizational Citizenship Behaviour (OCB). The method used in this research was a correlational descriptive method using a quantitative approach. The population in this research took 136 the non-permanent teachers who work seperatelly at 14 private junior high schools located in the district of Jonggol Bogor Regency. The sampling technique was using proportional random sampling in Slovin formula with 5% margin error with a sample amount of 102 teachers. This study resulted in a conclusion; 1) there was a positive relationship between the organizational commitment with OCB. The strength of the relationship between organizational commitment (X1) and OCB (Y) was demonstrated by the correlation coefficient ry1 = 0848 and the organizational commitment contributed 71.9% to the OCB, 2) There was a positive relationship between spiritual intelligence with OCB. The strength of the relationship between Spiritual Intelligence (X2) and OCB (Y) was demonstrated by the correlation coefficient ry2 = 0,786 and Spiritual Intelligence contributed 61.8% to the OCB, 3) There was a positive relationship between the organizational commitment (X1) and spiritual intelligence (X2) jointly with the OCB (Y) shown with the correlation coefficient ry12 = 0.848 and the organizational and intelligence commitments Spiritual collectively contributed 71.9% to the OCB. Based on the findings, the OCB of teachers can be improved through organizational commitment and spiritual intelligence.